Does the Daminozide Application Contribute to Improve Chrysanthemum Quality? - Sitawati Sitawati; A.N. Ni’mah (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2021)
Chrysanthemum or chrysanths is an ornamental plant with high market potential. The application frequency of gibberellins synthesis inhibitor (daminozide) as a growth regulator on growth and quality of flowering in three types of chrysanthemums was observed in this study. The research was conducted from June to October 2019 in Pasuruan, East Java, Indonesia. A split-plot design was chosen, with chrysanthemum pot as the main plot based on growth phase and daminozide frequency as subplots. PGR was sprayed on the leaves at a dose of 15 ml per plant or 4000 ppm with 0, 2, and 3 applications. The frequency of daminozide application was effective to control the plant height and vase life. The application of daminozide increases the palisade thickness and reduces the internodes number, giving the plant a muscular appearance. Three times (2, 4, 6 weeks after sowing), and twice (2 and 4 weeks after planting) daminozide application for Tobaga (fast-growing) and Time Jewel (moderate-growing) chrysanthemum, respectively are needed to increase quality based on the market standard. Application of daminozide is not required for Cosmo Magenta (slow-growing) to reach the standard height (ca. 18-24 cm).